2010
DOI: 10.4038/cmj.v55i3.2296
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life following restorative proctocolectomy for ulcerative colitis and familial adenomatous polyposis

Abstract: Research lettersUlcerative colitis (UC) is a chronic inflammatory bowel disease and familial adenomatous polyposis (FAP) is a hereditary disease of the colon. Both FAP and long standing UC carry an increased risk of colorectal cancer (CRC). At present, restorative proctocolectomy (RP) is the surgical treatment of choice for UC and for all patients with FAP. RP aims to remove the entire diseased colon and restore intestinal continuity by creating a neo-rectum with the terminal ileum [1,2]. It is a safe procedur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 9 publications
1
1
0
Order By: Relevance
“…When comparing the CGQL scores after one year of surgery against the indication, influence of pre-operative CGQL scores has to be controlled since quality of life of UC group is compromised due to presence of symptoms despite the medical treatment. Compared to a previous study [4], this study showed the same trend of mean CGQL scores preoperatively and post-operatively after one year. After controlling the influence of pre-operative CGQL scores, no significant difference of post-operative CGQL scores after one year of surgery was found implying that IPAA procedure is acceptable in both UC and FAP.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…When comparing the CGQL scores after one year of surgery against the indication, influence of pre-operative CGQL scores has to be controlled since quality of life of UC group is compromised due to presence of symptoms despite the medical treatment. Compared to a previous study [4], this study showed the same trend of mean CGQL scores preoperatively and post-operatively after one year. After controlling the influence of pre-operative CGQL scores, no significant difference of post-operative CGQL scores after one year of surgery was found implying that IPAA procedure is acceptable in both UC and FAP.…”
Section: Discussionsupporting
confidence: 70%
“…Duminda et al [4] in 2010 in a prospective study concluded that IPAA increases the CGQL scores in UC group significantly after 1 year. But no significant difference was found in FAP group.…”
Section: Discussionmentioning
confidence: 95%